Mandatory Bequests and Succession in Islamic Inheritance Law - Ritonga, Nurman; Putri, Nayla Amalia; Annisa, Putri; Fatihah, Nurul; Dewanto, Prayogi (El-Rusyd, 2026)
Death creates legal consequences in the form of the transfer of rights and obligations to heirs. In Islamic inheritance law, inheritance issues are not only related to the distribution of inheritance assets but also concern the protection of parties who may lose inheritance rights, such as orphaned grandchildren and relatives who do not receive inheritance shares. To address these issues of justice, Indonesian Islamic law has developed the concepts of compulsory bequest (wasiat wajibah) and substitute heirs as regulated in the Compilation of Islamic Law. This study aims to analyze the concepts, legal foundations, implementation, and relevance of compulsory bequests and substitute heirs in realizing justice within Islamic inheritance law in Indonesia. This research employs a normative legal research method with a library research approach. Data were collected from primary legal sources, including the Quran, Hadith, the Compilation of Islamic Law, and relevant court decisions, as well as secondary legal sources such as books, scientific journals, and previous studies. Data analysis was conducted descriptively and analytically through conceptual and statutory approaches. The findings indicate that compulsory bequests serve as a legal instrument to protect individuals who are not entitled to direct inheritance rights, such as adopted children, adoptive parents, and, in certain judicial practices, heirs of different religions. Meanwhile, substitute heirs represent a reform of Islamic inheritance law that allows grandchildren to replace the position of their deceased parents who passed away before the testator. Both concepts share the same objective of promoting justice, public welfare, and protection of family economic rights. Therefore, compulsory bequests and substitute heirs constitute forms of Islamic legal ijtihad that remain relevant to contemporary societal needs and are consistent with the principles of maqashid al-shariah in preserving wealth and lineage.